2017
DOI: 10.3389/fevo.2017.00071
|View full text |Cite
|
Sign up to set email alerts
|

Global Change and the Soil Microbiome: A Human-Health Perspective

Abstract: The importance of the gut and the soil microbiomes as determinants of human and ecosystem health, respectively, is gaining rapid acceptation in the medical and ecological literatures. This suggests that there is a wealth of highly transferable knowledge about the microbial ecology of human and non-human ecosystems that is currently being generated in parallel, but mostly in isolation from one another. I suggest that effectively sharing this knowledge could greatly help at more efficiently understanding and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…We then showed that using an unbiased search of the entire release of UniProt (ca. 90 million protein sequences ) 1 MetaNovo was able to identify a similar bacterial taxonomic distribution compared to that found using a small, focused matched metagenome database, but now also simultaneously identified proteins present in the samples that are derived from other organisms missed by 16S or shotgun sequencing and by previous metaproteomic methods . Using MetaNovo to analyze a set of single-organism human neuroblastoma cell-line samples ( SH-SY5Y ) against Introduction Characterizing complex mass-spectrometry data from clinical or environmental samples allows for potential insights into the complex metabolic pathways involved in processes as diverse as carbon sequestration and climate change to the susceptibility and progression of human diseases.…”
Section: Introductionmentioning
confidence: 70%
“…We then showed that using an unbiased search of the entire release of UniProt (ca. 90 million protein sequences ) 1 MetaNovo was able to identify a similar bacterial taxonomic distribution compared to that found using a small, focused matched metagenome database, but now also simultaneously identified proteins present in the samples that are derived from other organisms missed by 16S or shotgun sequencing and by previous metaproteomic methods . Using MetaNovo to analyze a set of single-organism human neuroblastoma cell-line samples ( SH-SY5Y ) against Introduction Characterizing complex mass-spectrometry data from clinical or environmental samples allows for potential insights into the complex metabolic pathways involved in processes as diverse as carbon sequestration and climate change to the susceptibility and progression of human diseases.…”
Section: Introductionmentioning
confidence: 70%
“…The human microbiome includes all those bacteria, archaea, fungi, protists, and viruses that colonize, among others, human skin, placenta, uterus, seminal fluid, lungs, saliva, oral mucosa, conjunctiva, and especially the gastrointestinal tract. If we view the human as an integrated ecosystem with its microbiome [31] -a holobiont [32][33][34][35][36] then, the microbiome renders a vast array of ecosystem services. [37] By ecosystem services we mean that the human microbiome stimulates the immune system and shapes its development, [38][39][40] contributes to the development and functioning of the nervous system, [41][42][43] the synthesis of micronutrients, [44] nutrient digestion and absorption, and to energy regulation.…”
Section: From Diet To Phenotype Through the Microbiomementioning
confidence: 99%
“…If desired plant traits (e.g., drought tolerance) can be provided or enhanced by using a microbial partner, early collaboration would likely lead to greater success and save limited research resources. Broader multidisciplinary research is needed to fully understand the potential effect of new pasture cultivars/microbiome associations within the wider ecosystem (e.g., Duckworth et al 2017;Ochoa-Hueso 2017). Equally, as with any technological changes, questions around the unintended impacts will also need to be answered; for example, "what are the potential effects on other beneficial microbes in soil and plant?…”
Section: Figurementioning
confidence: 99%